Physical and Mechanical Properties of Eucalyptus grandis and E. Tereticornis Grown in Kerala - Brat, K. M.; Thulasidas, P. K. (Indian Forester, 1997)
Physical and mechanical testing of 30-year-old Eucalyptus grandis and 16-year-old E. tereticornis reveals that timber of the former is lighter and weaker than the latter. Shrinkage appears to begin in the early stage of drying when the moisture content is above 50-60%. Both the species show about 80-95% of the bending and 66-81 % of the compression (parallel to grain) strength values of mature teak indicating their suitability for solid wood uses. As compared with the reported values of bending strength, E. tereticornis is found about 11% weaker than that grown in drier localities of North India.